Injuries in team sport tournaments during the 2004 Olympic Games - Junge, A.; Langevoort, G.; Pipe, A.; Peytavin, A.; Wong, F.; Mountjoy, M.; Beltrami, G.; Terrell, R.; Holzgraefe, M.; Charles, R.; Dvorak, J. (The American Journal of Sports Medicine, 2005)
Several authors have analyzed the incidence of injuries in a given sport, but only a few have examined the exposure-related incidence of injuries in different types of sports using the same methodology.